2021
DOI: 10.1002/mrm.29096
|View full text |Cite
|
Sign up to set email alerts
|

A nine‐channel transmit/receive array for spine imaging at 10.5 T: Introduction to a nonuniform dielectric substrate antenna

Abstract: The purpose of this study is to introduce a new antenna element with improved transmit performance, named the nonuniform dielectric substrate (NODES) antenna, for building transmit arrays at ultrahigh-field. Methods:We optimized a dipole antenna at 10.5 Tesla by maximizing the B + 1 -SAR efficiency in a phantom for a human spine target. The optimization parameters included permittivity variation in the substrate, substrate thickness, antenna length, and conductor geometry. We conducted electromagnetic simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…As we move up the mountain face, we should pause for a moment to acknowledge and applaud the pioneers who climbed the very steep mountains to 9.4 T [33], 10.5 T [8,37,38] and 11.7 T [39]. These explorers were essentially free climbing, reaching the summit without vendor-provided RF coils and without push-button software, yet nevertheless navigating through the enormous challenges towards beautiful images of the brain and the body enabled by parallel transmission.…”
Section: Sending and Receiving Signals During The Climbmentioning
confidence: 99%
“…As we move up the mountain face, we should pause for a moment to acknowledge and applaud the pioneers who climbed the very steep mountains to 9.4 T [33], 10.5 T [8,37,38] and 11.7 T [39]. These explorers were essentially free climbing, reaching the summit without vendor-provided RF coils and without push-button software, yet nevertheless navigating through the enormous challenges towards beautiful images of the brain and the body enabled by parallel transmission.…”
Section: Sending and Receiving Signals During The Climbmentioning
confidence: 99%
“…Furthermore, ceramic materials can be currently developed in an impressively wide range of dielectric constants and electrical conductivities, and this should provide a motivation to explore such structures in the context of novel RF concepts tailored for different B 0 field strengths. Also, note that the dielectric block does not necessarily have to be designed as a homogeneous structure 37 ; mixing dielectric materials of different electrical properties could be considered as promising aspect of the future DRA optimizations. The same applies to the geometry of the dipole antenna and the distribution of the lumped components on the antenna.…”
Section: Discussionmentioning
confidence: 99%
“…16 or 24), inter-element coupling can be problematic, and additional RF shields were used in their simulations. A similar approach was proposed by Sadeghi-Tarakameh et al who showed that combining dipole antennas with optimized dielectric blocks can be a promising solution for MRI at 10.5 T [26].…”
Section: Introductionmentioning
confidence: 93%